Human Capital Formation, Income Inequality and Growth - Jean-Marie Viaene; Itzhak Zilcha (Center for Economic Studies and ifo Institute (CESifo), 2001)
The paper studies the determinants of income distribution and growth in an overlapping generations economy with heterogenous households. Our framework has the following main features: (1) heterogeneity of consumers with respect to wealth and parental human capital; (2) intergenerational transfers are accomplished via investment in the education of the younger generation. Heterogeneity in income results from the distribution of human capital across individuals in a nondegenerate way. The human capital production is affected by the 'home-education', provided by the parents, as well as the 'public-education' which is provided equally to all young individuals of the same generation. Due to investments in human capital our economy is an endogenous growth model. First, we explore the effects of technological improvements in the human capital process, upon the distribution of income at each date along the equilibrium path. Second, we study the impact of such technogical progress on growth and relate these results to the income distribution inequality. Third, we provide numerical simulations to quantify the effect of changes in the parameters of the model. Simulation results include exact Gini coefficients and tax rate on labor determined endogenously through majority voting.
Keywords: 330; Human Capital; income distribution; endogenous growth